Preparation method of Al2O3 coated xWyMo composite powder

Through the preparation method of Al2O3 coated xWyMo composite powder, the low-temperature brittleness and uneven distribution of tungsten-molybdenum composite material were solved, and the uniformity and performance of the material were improved, forming a regular morphology and high-strength composite powder. .

CN119187557APending Publication Date: 2024-12-27HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410919833.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the use of existing tungsten-molybdenum composite materials, there are problems of low-temperature brittleness, radiation brittleness and recrystallization brittleness, resulting in limited performance excellence, and alumina is prone to agglomeration in composite powders, resulting in uneven distribution.

Method used

The preparation method of Al2O3 coated xWyMo composite powder was adopted, and the hydrothermal reaction was obtained by adding dilute aqueous nitric acid solution to the mixed solution of ammonium metatungstate and ammonium molybdate to obtain a mixed suspension of WO3·0.33H2O and MoO3·0.34H2O. The hydrothermal reaction is carried out in a mixed solution of aluminum nitrate and triammonium citrate, followed by freeze-drying and calcining to form a uniform spherical Al2O3 coated structure to avoid agglomeration.

Benefits of technology

The uniformity and morphological regularity of the composite powder are improved, the strength, hardness and ductility of the material are enhanced, and the Al elements are evenly distributed around W and Mo, avoiding the agglomeration of the composite powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187557A_ABST
    Figure CN119187557A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of Al2O3 coated xWyMo composite powder, which comprises the following steps: 1) adding a dilute nitric acid aqueous solution into a mixed solution of ammonium metatungstate and ammonium molybdate to obtain an acidic mixed solution A, and carrying out hydrothermal reaction on the mixed solution A to obtain a mixed turbid liquid B of WO3. 0.33 H2O and MoO3. 0.34 H2O; (2) adding the WO3. 0.33 H2O and MoO3. 0.34 H2O mixed turbid liquid B obtained in the step (1) into a mixed solution C of aluminum nitrate and triammonium citrate, and adding an ethanol water solution for hydrothermal reaction to obtain a mixed turbid liquid D; 3) performing freeze drying on the mixed suspension D under the condition of-30 to-20 DEG C to obtain coated powder; and 4) calcining the coated powder at 500-600 DEG C, reducing the coated powder at 500-560 DEG C and reducing the coated powder at 890-960 DEG C in sequence to obtain the Al2O3 coated xWyMo composite powder. According to the Al2O3 coated xWyMo composite powder disclosed by the invention, aluminum oxide and tungsten-molybdenum alloy form a coated structure, so that the uniformity of the composite powder is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tungsten-molybdenum composite materials, in particular to a method for preparing Al2O3-coated xWyMo composite powder. Background Art

[0002] Tungsten, molybdenum and their alloys have the advantages of high melting point, high temperature strength and good high temperature hardness. They are important structural materials in the high temperature field and are widely used in defense, aviation, shipbuilding and energy fields. However, tungsten-molybdenum alloys have problems such as low-temperature brittleness, radiation brittleness and recrystallization brittleness during use, which limit the performance excellence of tungsten, molybdenum and their alloys to varying degrees.

[0003] Therefore, in 2021, the applicant proposed a method for preparing molybdenum / alumina doped tungsten composite powder and high-strength and toughness tungsten alloy. The introduction of alumina to achieve dispersion strengthening can improve the strength and thermal stability of the tungsten alloy. However, in the composite body prepared by this method, alumina is prone to agglomeration, resulting in uneven distribution of alumina, tungsten and molybdenum. Summary of the invention

[0004] In order to solve the problem of uneven distribution of composite powder in the prior art, the present invention provides a method for preparing Al2O3-coated xWyMo composite powder, in which aluminum oxide and tungsten-molybdenum alloy form a coating structure, which improves the uniformity of the composite powder.

[0005] In order to achieve the above object, the specific scheme adopted by the present invention is: a method for preparing Al2O3-coated xWyMo composite powder, comprising the following steps:

[0006] 1) adding a dilute nitric acid aqueous solution to a mixed solution of ammonium metatungstate and ammonium molybdate to obtain an acidic mixed solution A, and subjecting the mixed solution A to a hydrothermal reaction to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O;

[0007] 2) adding the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) to the mixed solution C of aluminum nitrate and triammonium citrate, and adding ethanol aqueous solution for hydrothermal reaction to obtain a mixed suspension D;

[0008] 3) freeze-drying the mixed suspension D at -30 to -20°C to obtain coated powder;

[0009] 4) The coated powder is calcined at 500-600° C., reduced at 500-560° C. and 890-960° C. in sequence to obtain Al2O3-coated xWyMo composite powder.

[0010] As an optimized solution for the preparation method of the above-mentioned Al2O3-coated xWyMo composite powder: in the step 1), the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.1-0.5 g / mL.

[0011] As another optimized solution of the preparation method of the above-mentioned Al2O3-coated xWyMo composite powder: in the step 1), the ratio of tungsten atoms to molybdenum atoms in the mixed solution A is 1:1.

[0012] As another optimized solution of the preparation method of the above-mentioned Al2O3-coated xWyMo composite powder: in the step 1), the reaction temperature of the hydrothermal reaction is 90-190°C and the reaction time is 10-25h.

[0013] As another optimized solution of the above-mentioned method for preparing the Al2O3-coated xWyMo composite powder: in the step 1), the pH of the mixed solution A is 0-1.

[0014] As another optimized solution of the above-mentioned method for preparing the Al2O3-coated xWyMo composite powder: in the step 2), the molar ratio of aluminum ions to citrate ions in the mixed solution C is 2:1-5:1.

[0015] As another optimized solution of the above-mentioned method for preparing the Al2O3-coated xWyMo composite powder: in the step 2), the volume ratio of the mixed solution C and the ethanol aqueous solution is 1-3:1.

[0016] As another optimized solution of the above-mentioned method for preparing the Al2O3-coated xWyMo composite powder: in the step 2), the total concentration of aluminum nitrate and triammonium citrate in the mixed solution C is 0.1-0.5 g / mL.

[0017] As another optimized solution of the preparation method of the above-mentioned Al2O3-coated xWyMo composite powder: in the step 2), the reaction temperature of the hydrothermal reaction is 90-190°C and the reaction time is 5-25h.

[0018] As another optimized solution of the preparation method of the above-mentioned Al2O3-coated xWyMo composite powder: the mixed suspension D is freeze-dried at -30°C to obtain the coated powder.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention provides a preparation method of Al2O3 coated xWyMo composite powder. Dilute nitric acid is added to ammonium metatungstate and ammonium molybdate for hydrothermal reaction to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O. The obtained mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O is added to a mixed solution B of aluminum nitrate and triammonium citrate, and ethanol is used as a dispersant for hydrothermal reaction to obtain a mixed suspension D. The mixed suspension D is cooled at -30 to -20°C. Freeze drying obtains coated powder formed by A1O(OH) coating WO3·0.33H2O and MoO3·0.34H2O; A1O(OH) combines with WO3·0.33H2O and MoO3·0.34H2O to generate Al2(WO4)3 and Al2(MoO4)3 in subsequent calcination, and at the same time, the Al element is always evenly distributed around W and Mo; thereby improving the uniformity of spherical Al2O3 coated WMo powder and avoiding agglomeration of the composite powder; at the same time, the morphology of the composite powder is more regular. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the preparation process of WMo-Al2O3 powder;

[0022] Figure 2 This is the TEM image of Al2O3 coated WMo powder;

[0023] Figure 3 This is the TEM image of the interface of Al2O3 coated WMo powder

[0024] Figure 4 This is the TEM image of Al2O3 coated WMo powder;

[0025] Figure 5 This is the EDS scan of W in WMo-Al2O3 powder;

[0026] Figure 6 This is the EDS scan of Mo in WMo-Al2O3 powder;

[0027] Figure 7 This is the EDS scan of Al in WMo-Al2O3 powder;

[0028] Figure 8 This is the EDS scan of O in WMo-Al2O3 powder;

[0029] Fig. 9 This is the EDS point scan of Al2O3 in WMo-Al2O3 powder. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.

[0031] A method for preparing Al2O3-coated xWyMo composite powder, characterized in that it comprises the following steps:

[0032] 1) Adding a dilute nitric acid aqueous solution to a mixed solution of ammonium metatungstate and ammonium molybdate to obtain an acidic mixed solution A, and subjecting the mixed solution A to a hydrothermal reaction to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O; wherein the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.1-0.5 g / mL, the ratio of tungsten atoms to molybdenum atoms in the mixed solution A is 1:1, the pH of the mixed solution A is 0-1, the reaction temperature of the hydrothermal reaction is 110-190° C., and the reaction time is 10-25 h;

[0033] 2) adding the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) to a mixed solution C of aluminum nitrate and triammonium citrate, and adding an ethanol aqueous solution for hydrothermal reaction, wherein the volume ratio of the mixed solution C to the ethanol aqueous solution is 1-3:1, to obtain a mixed suspension D, wherein the total concentration of aluminum nitrate and triammonium citrate in the mixed solution C is 0.1-0.5 g / mL, the molar ratio of aluminum ions to citrate ions in the mixed solution C is 2:1-5:1, and the reaction temperature of the hydrothermal reaction is 110-190°C and the reaction time is 5-25h;

[0034] 3) The mixed suspension D is freeze-dried at -30 to -20°C to obtain a coated powder, wherein the coated powder is a powder of WO3·0.33H2O and MoO3·0.34H2O coated with A1O(OH);

[0035] 4) The coated powder is calcined at 500-600°C, reduced at 500-560°C and 890-960°C in sequence to obtain Al2O3-coated xWyMo composite powder. Specifically, the coated powder is calcined at 500-600°C for 4-6h to obtain WO3 / MoO3 / Al2O3 composite powder; then the first stage of reduction is performed: the WO3 / MoO3 / Al2O3 composite powder is reduced in a hydrogen atmosphere at 500-560°C for 4-8h to obtain WO2 / MoO2 / Al2O3 composite powder; the second stage of reduction is performed: the WO2 / MoO2 / Al2O3 composite powder is reduced in a hydrogen atmosphere at 900-980°C for 4-8h to obtain WMo-Al2O3 composite powder.

[0036] In the present invention, the prepared spherical Al2O3 has a particle size of 5-15nm, the WMo has a particle size of 100-500nm, and the particle size distribution is uniform, so that the WMo-Al2O3 composite powder has good solid solubility and improves the strength, hardness and ductility of the material.

[0037] Mo is used as a solid solution element to make the hydrothermal reaction product of ammonium metatungstate and ammonium molybdate solid solution at the atomic level. Nano-A1O(OH) is the second phase to inhibit the growth of grains and has a significant effect of refining particles. The powder prepared by this method is uniform and the particle size can be controlled at the nanometer level. In this method, A1O(OH) combines with WO3·0.33H2O and MoO3·0.34H2O to generate Al2(WO4)3 and Al2(MoO4)3, so that the Al element is always evenly distributed around W and Mo; at the same time, the mixed suspension D is freeze-dried to obtain a coated powder, thereby improving the uniformity of the spherical Al2O3 coated WMo powder and avoiding the agglomeration of the composite powder; at the same time, the morphology of the composite powder is more regular.

[0038] In the present invention, the atomic ratio between tungsten and molybdenum in the spherical Al2O3-coated xWyMo composite powder can reach any ratio.

[0039] Example 1

[0040] 1) Add 70 mL of dilute nitric acid aqueous solution to 4.135 g of ammonium metatungstate and 2.847 g of ammonium molybdate to obtain a mixed solution A, wherein the pH value of the mixed solution A is 0, and the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.1 g / mL. The mixed solution is placed in a high-pressure reactor and subjected to a hydrothermal reaction at 110° C. for 25 h to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O.

[0041] 2) 6.02 g of aluminum nitrate and 0.98 g of triammonium citrate were added to 70 mL of distilled water to prepare a mixed solution C with a concentration of 0.1 g / mL, 70 mL of ethanol aqueous solution was added to the mixed solution C, and the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) was slowly added to the mixed solution C while stirring during the addition process. After stirring for 8 hours, a mixed solution was obtained, and a hydrothermal reaction was performed at 110° C. for 25 hours to obtain a mixed suspension D;

[0042] 3) The mixed suspension D was freeze-dried at -30°C for 8 h to obtain a coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O;

[0043] 4) The coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O was calcined at 500℃ for 4h to obtain WO3 / MoO3 / Al2O3 composite powder; then, the first stage reduction was carried out: the WO3 / MoO3 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 500℃ for 4h to obtain WO2 / MoO2 / Al2O3 composite powder; the second stage reduction: the WO2 / MoO2 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 890℃ for 4h to obtain WMo-Al2O3 composite powder.

[0044] In the present invention, the particle size of the prepared spherical Al2O3 is 10-15nm, and the particle size of WMo is 100-500nm.

[0045] Through TEM structural characterization test, the TEM image of WMo-Al2O3 composite powder obtained in this embodiment is as follows Figure 2 shown.

[0046] Example 2

[0047] 1) 70 mL of dilute nitric acid solution was added to 12.45 g of ammonium metatungstate and 8.55 g of ammonium molybdate to obtain a mixed solution A, wherein the pH value of the mixed solution A was 0.5, and the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A was 0.3 g / mL. The mixed solution was placed in a high pressure reactor and subjected to a hydrothermal reaction at 110° C. for 25 h to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O.

[0048] 2) 18.06 aluminum nitrate and 2.94 triammonium citrate were added to 70 mL of distilled water to prepare a mixed solution C with a concentration of 0.3 g / mL, 140 mL of ethanol aqueous solution was added to the mixed solution B, and the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) was slowly added to the mixed solution C while stirring during the addition process, and a mixed solution was obtained after stirring for 16 hours, and a hydrothermal reaction was carried out at 190° C. for 25 hours to obtain a mixed suspension D;

[0049] 3) The mixed suspension D was freeze-dried at -20°C for 16 h to obtain a coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O;

[0050] 4) The coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O was calcined at 550°C for 5h to obtain WO3 / MoO3 / Al2O3 composite powder; then, the first reduction was carried out: the WO3 / MoO3 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 530°C for 6h to obtain WO2 / MoO2 / Al2O3 composite powder; the second reduction: the WO2 / MoO2 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 920°C for 6h to obtain WMo-Al2O3 composite powder.

[0051] In the present invention, the particle size of the prepared spherical Al2O3 is 8-14nm, and the particle size of WMo is 100-450nm.

[0052] Example 3

[0053] 1) Add 70 mL of dilute nitric acid solution to 20.75 g of ammonium metatungstate and 14.25 g of ammonium molybdate to obtain a mixed solution A, wherein the pH value of the mixed solution A is 0.5, and the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.5 g / mL. The mixed solution is placed in a high pressure reactor and subjected to a hydrothermal reaction at 170° C. for 15 h to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O.

[0054] 2) 30.01 g of aluminum nitrate and 4.90 g of triammonium citrate were added to 70 mL of distilled water to prepare a mixed solution C with a concentration of 0.5 g / mL, 210 ml of ethanol was added to the mixed solution C, and the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) was slowly added to the mixed solution C while stirring during the addition process. After stirring for 16 hours, a mixed solution was obtained, and a hydrothermal reaction was carried out at 170° C. for 15 hours to obtain a mixed suspension D;

[0055] 3) The mixed suspension D was freeze-dried at -30°C for 24 h to obtain a coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O;

[0056] 4) The coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O was calcined at 600℃ for 6h to obtain WO3 / MoO3 / Al2O3 composite powder; then, the first stage reduction was carried out: the WO3 / MoO3 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 560℃ for 8h to obtain WO2 / MoO2 / Al2O3 composite powder; the second stage reduction: the WO2 / MoO2 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 960℃ for 8h to obtain WMo-Al2O3 composite powder.

[0057] In the present invention, the particle size of the prepared spherical Al2O3 is 7-13nm, and the particle size of WMo is 300-460nm.

[0058] Example 4

[0059] 1) Add 70 mL of dilute nitric acid solution to 8.3 g of ammonium metatungstate and 4.98 g of ammonium molybdate to obtain a mixed solution A, wherein the pH value of the mixed solution A is 1, and the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.2 g / mL. The mixed solution is placed in a high-pressure reactor and subjected to a hydrothermal reaction at 150° C. for 20 h to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O.

[0060] 2) 12.04 g of aluminum nitrate and 1.96 g of triammonium citrate were added to 70 mL of distilled water to prepare a mixed solution C with a concentration of 0.2 g / mL. The mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) was slowly added to the mixed solution C with 70 mL of ethanol in the mixed solution C, and the mixture was stirred during the addition process. After stirring for 16 hours, a mixed solution was obtained, and a hydrothermal reaction was performed at 150° C. for 20 hours to obtain a mixed suspension D;

[0061] 3) The mixed suspension D was freeze-dried at -30°C for 10 h to obtain a coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O;

[0062] 4) The coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O was calcined at 550°C for 5h to obtain WO3 / MoO3 / Al2O3 composite powder; then, the first stage of reduction was performed: the WO3 / MoO3 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 550°C for 5h to obtain WO2 / MoO2 / Al2O3 composite powder; the second stage of reduction was performed: the WO2 / MoO2 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 920°C for 8h to obtain WMo-Al2O3 composite powder. Through TEM structural characterization testing, the TEM image of the WMo-Al2O3 composite powder obtained in this embodiment is as follows: Figure 3 shown.

[0063] Example 5

[0064] 1) Add 70 mL of dilute nitric acid solution to 16.6 g of ammonium metatungstate and 9.96 g of ammonium molybdate to obtain a mixed solution A, wherein the pH value of the mixed solution A is 1, and the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.4 g / mL. The mixed solution is placed in a high-pressure reactor and subjected to a hydrothermal reaction at 130° C. for 10 h to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O.

[0065] 2) 24.08 g of aluminum nitrate and 3.92 g of triammonium citrate were added to 70 mL of distilled water to prepare a mixed solution C with a concentration of 0.2 g / mL. 140 mL of ethanol was added to the mixed solution C, and the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) was slowly added to the mixed solution C while stirring during the addition process. After stirring for 15 hours, a mixed solution was obtained, and a hydrothermal reaction was performed at 130° C. for 10 hours to obtain a mixed suspension D;

[0066] 3) The mixed solution C was freeze-dried at -30°C for 15 h to obtain a coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O;

[0067] 4) The coated powder formed by A1O(OH)-coated WO3·0.33H2O and MoO3·0.34H2O was calcined at 520°C for 5h to obtain WO3 / MoO3 / Al2O3 composite powder; then, the first stage of reduction was performed: the WO3 / MoO3 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 540°C for 4h to obtain WO2 / MoO2 / Al2O3 composite powder; the second stage of reduction was performed: the WO2 / MoO2 / Al2O3 composite powder was reduced in a hydrogen atmosphere at 920°C for 6h to obtain WMo-Al2O3 composite powder. Through TEM structural characterization testing, the TEM image of the WMo-Al2O3 composite powder obtained in this embodiment is as follows: Figure 3 shown.

[0068] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing Al2O3-coated xWyMo composite powder, characterized in that: The following steps are involved: 1) adding a dilute nitric acid aqueous solution to a mixed solution of ammonium metatungstate and ammonium molybdate to obtain an acidic mixed solution A, and subjecting the mixed solution A to a hydrothermal reaction to obtain a mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O; 2) adding the mixed suspension B of WO3·0.33H2O and MoO3·0.34H2O obtained in step 1) to the mixed solution C of aluminum nitrate and triammonium citrate, and adding ethanol aqueous solution for hydrothermal reaction to obtain a mixed suspension D; 3) freeze-drying the mixed suspension D at -30 to -20°C to obtain coated powder; 4) The coated powder is calcined at 500-600° C., reduced at 500-560° C. and 890-960° C. in sequence to obtain Al2O3-coated xWyMo composite powder.

2. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 1), the total concentration of ammonium metatungstate and ammonium molybdate in the mixed solution A is 0.1-0.5 g / mL.

3. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 1), the ratio of tungsten atoms to molybdenum atoms in the mixed solution A is 1:

1.

4. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 1), the reaction temperature of the hydrothermal reaction is 90-190° C. and the reaction time is 10-25 h.

5. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 1), the pH of the mixed solution A is 0-1.

6. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 2), the molar ratio of aluminum ions to citrate ions in the mixed solution C is 2:1-5:

1.

7. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 2), the volume ratio of the mixed solution C to the ethanol aqueous solution is 1-3:

1.

8. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 2), the total concentration of aluminum nitrate and triammonium citrate in the mixed solution C is 0.1-0.5 g / mL.

9. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: In the step 2), the reaction temperature of the hydrothermal reaction is 90-190° C. and the reaction time is 5-25 h.

10. The method for preparing an Al2O3-coated xWyMo composite powder according to claim 1, characterized in that: The mixed suspension D was freeze-dried at -30°C to obtain coated powder.